Type 2 immune responses are associated with less severe COVID-19 in a hospitalized cohort - Naresh Doni Jayavelu, PhD; Jingjing Qi, MSc; Carly E. Milliren, MPH; Al Ozonoff, PhD; Shanshan Liu, MPH; Ofer Levy, MD, PhD; Lindsey R. Baden, MD; Esther Melamed, MD, PhD; Grace A. McComsey, MD; Charles B. Cairns, MD; Joanna Schaenman, MD, PhD; Albert C. Shaw, MD, PhD; et al. (Journal of Allergy and Clinical Immunology: Global, 2025)
Background: The novel coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spread rapidly after its identification in December 2019 to cause a global pandemic. The respiratory tract is the primary site of infection, and there is a large range in the severity of respiratory illnesses caused by the virus. Defining molecular and cellular factors for protection from severe disease and death has been a goal to better understand and to predict and mitigate the effects of SARS-CoV-2 and future coronaviruses. Objective: Despite well-known susceptibilities to respiratory viral infections, respiratory allergy and allergic asthma have not been identified as risk factors for severe coronavirus disease 2019 (COVID-19) in most epidemiologic studies and may be protective. We sought to investigate associations between markers of type 2 (T2) immune responses with SARS-CoV-2 clinical outcomes and virus loads in a cohort of 1164 individuals hospitalized for COVID-19 from May 2020 to March 2021 as part of the IMPACC study. Methods: We characterized the clinical outcomes, as defined by severity trajectory groups reflecting the degree of respiratory support required, virus loads, and antibody titers of COVID-19 infections in IMPACC participants in relation to molecular and cellular markers of T2 immune responses through multiple assays, including, (1) IL-4, IL-5, and IL-13 levels in serum Olink data, (2) T2 cellular signatures in blood cytometry by time of flight data, (3) relative quantification of T2 signaling gene pathways in airway RNA sequencing data, and/or (4) T2 pathways in peripheral blood mononuclear cell RNA sequencing data. We also investigated the outcomes of individuals with self-reported asthma and evidence of T2 immune responses. Results: The diagnosis of asthma (odd ratio = 1.27), elevated serum T2 cytokine levels (median fold change = 1.06), and a higher frequency of TH2 cells (difference = +2%) were associated with less severe clinical disease during hospitalization. Distinct T2-related transcriptomic changes in nasal and blood samples were associated with reduced virus loads. This included the expression of T2-regulated genes implicated in T-/B-cell activation and apoptosis in nasal samples and the expression of T2-regulated genes implicated in myeloid differentiation and reactive oxygen species signaling in blood. Among these, several canonical T2-regulated genes that were increased in less severe disease were identified to have antiviral properties in large high-throughput screens. Conclusion: T2 immune responses were associated with lower virus loads and more favorable clinical outcomes, suggesting that T2 inflammation related to asthma and allergic diseases may have a direct protective effect against SARS-CoV-2.